A Case of Rituximab Use as an Induction and Maintenance of Remission in ANCA-Associated Vasculitis - Neveen Awad; Shahd Hafiz; Abdurahman Albeity; Hani Almoallim (Case Reports in Rheumatology)
Antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV) is a multisystem autoimmune disease affecting mainly microscopic blood vessels due to circulating autoantibodies against neutrophil cytoplasmic antigens. We report a case of a 57-year-old female patient presenting with hemoptysis, sinusitis, and conjunctivitis. Based on lung biopsy, the diagnosis of antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV) was established. She was put on rituximab as induction and maintenance therapy. She responded initially to rituximab as induction therapy but failed to respond in the maintenance course of the drug. Rituximab was stopped and mycophenolate mofetil was administered. She responded as laboratory c-ANCA titers turned negative and symptoms subsided. There are no randomized clinical trials addressing rituximab effect in induction and remission at the same time. This case report doubts the efficacy of the use of rituximab therapy for both induction and maintenance of remission at the same time, waiting for the results of the ongoing trials.